2015
DOI: 10.2147/dddt.s80407
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ramosetron versus ondansetron for postoperative nausea and vomiting after general anesthesia: a meta-analysis of randomized clinical trials

Abstract: BackgroundPostoperative nausea and vomiting is a common side effect of general anesthesia. In this study, we performed a meta-analysis on the efficacy and safety of ramosetron versus ondansetron in the prevention of postoperative nausea and vomiting using the most recently published randomized controlled clinical studies.MethodsPubMed and EMBASE were searched for randomized controlled clinical trials comparing the efficacy and safety of ramosetron and ondansetron. The meta-analysis was performed using Review M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Previously, we reported results of the meta-analysis of the effects of ramosetron in preventing PON and POV [ 3 ]; the combined results with 637 patients (six studies) showed that ramosetron had a statistically significant effect on early POV (risk ratio [95% confidence interval] = 0.50 [0.28–0.90]) and late POV (0.53 [0.34–0.81]) but not early PON (0.79 [0.51–1.23]) and late PON (0.78 [0.60–1.46]) compared with 4 mg of ondansetron. Although ramosetron was reported to be more effective than ondasetron in preventing POV [ 3 , 4 ], an updated meta-analysis is required because several randomized controlled trials (RCTs) have been published since then. The Cochrane Handbook recommends that systematic reviews be updated within two years, because “systematic reviews that are not maintained may become out of date or misleading” [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported results of the meta-analysis of the effects of ramosetron in preventing PON and POV [ 3 ]; the combined results with 637 patients (six studies) showed that ramosetron had a statistically significant effect on early POV (risk ratio [95% confidence interval] = 0.50 [0.28–0.90]) and late POV (0.53 [0.34–0.81]) but not early PON (0.79 [0.51–1.23]) and late PON (0.78 [0.60–1.46]) compared with 4 mg of ondansetron. Although ramosetron was reported to be more effective than ondasetron in preventing POV [ 3 , 4 ], an updated meta-analysis is required because several randomized controlled trials (RCTs) have been published since then. The Cochrane Handbook recommends that systematic reviews be updated within two years, because “systematic reviews that are not maintained may become out of date or misleading” [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Cochrane Handbook recommends that systematic reviews be updated within two years, because “systematic reviews that are not maintained may become out of date or misleading” [ 5 ]. In addition, these previous studies [ 3 , 4 ] looked only at RCTs which prescribed 4 mg of ondansetron. Ryu et al reported that 8 mg of ondansetron were equally as effective as ramosetron in preventing PONV [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with a previous meta-analysis in which ramosetron was found to be more effective for PONV with fewer side effects in comparison with ondansetron. Aprepitant showed no statistically significant differences in reducing PON incidence (25). Secondly, fosaprepitant appeared to be the most effective prophylactic medication for POV, both between 0-24 and 0-48 h postoperatively.…”
Section: Discussionmentioning
confidence: 82%
“…In a recent meta-analysis comparing ramosetron to ondansetron for preventing PONV during various types of surgery, there was no difference in incidence of nausea, need for rescue antiemetics, and incidence of side effects, but there was significantly less vomiting in patients receiving ramosetron during early (0–6 h) and late (6–24 h) time periods. 14 16 In this study, we had expected that ramosetron would have an advantage over ondansetron in treating vomiting or preventing further retching or vomiting in the late period because differences exist in receptor affinity, pharmacokinetics, and the half-life between ramosetron and ondansetron (9 vs 3.5 h, respectively). 17 Although differences did not reach statistical significance, 53% of patients receiving ramosetron treatment were prevented from further retching or vomiting without secondary rescue antiemetic administration compared to 44% of patients receiving ondansetron treatment.…”
Section: Discussionmentioning
confidence: 99%